Case Report: A case of Salmonella spondylitis masquerading as tuberculosis in a child - Guo, Shuai; Zhu, Yu (Frontiers in Medicine, 2026)
BackgroundSalmonella typically causes gastroenteritis and rarely leads to invasive infections.Case presentationA 14-year-old boy, without a definitive history of an unsanitary diet or open wounds, was residing in an area with a high prevalence of tuberculosis. His primary symptoms included fever, cough, lumbar pain, and weight loss. The initial pathogen test was negative. Medical imaging revealed pulmonary nodules, intervertebral space narrowing, vertebral bone destruction, and a psoas muscle abscess. Empirical antibiotic therapy and diagnostic anti-tuberculosis treatment yielded poor results. Ultimately, pathogen testing of the surgically excised lesion identified Salmonella Dublin. Antimicrobial therapy guided by susceptibility testing yielded favorable outcomes.ConclusionEmpirical therapy is often necessary during the initial phase of treatment. However, clinicians should consider uncommon conditions and employ appropriate approaches to obtain pathogen-specific test results, which can guide targeted therapeutic strategies when the anticipated clinical outcome is suboptimal.